Cultural and Morphological Features of Trametes versicolor (Polyporaceae) Growth on Wood Hydrolyzes Containing Media - Zubyk, Pavlo; Klechak, Inna (Innovative Biosystems and Bioengineering, 2023)
Background. Trametes versicolor is a representative of basidiomycota, whose biologically active compounds are used in medicine and industry, so the search for active producers capable of growing on industrial waste and the study of new ways of intensification of growth and synthesis of metabolites are relevant task. Objective. Investigation of the effect of Fagales sawdust extracts on growth, morphological characteristics, and induction of synthesis of oxidizing enzymes by macromycetes of the species T. versicolor in surface culture. Methods. The objects of research were 5 strains of T. versicolor, which were cultivated on the synthetic agarized Norcrans media on Petri dishes. The influence of the sawdust extracts of 3 tree species, which acted as a basis for research media, was studied. The following cultural indicators were investigated: colony size, radial growth rate, and growth rate. The research also covered the study of macromycetes’ morphological characteristics and the ability of Fagales sawdust extracts to induce the synthesis of oxidative enzymes. Results. It is established that growth on media with the addition of birch extract is more intense: the radial growth rate is 11.2–13.6 mm/day, while for beech and oak, the growth rate ranges from 11.6–13.1 and 11.5–12.6 mm/day respectively. The highest growth value on all media is recorded for T. versicolor 353. The value of the growth rate on the medium with birch sawdust extracts varied in the range 15.8–92.1, for medium with beech extracts – 19.4–46.1, with oak extracts – 15.5–46,7, and the highest growth value was recorded during the cultivation of T. versicolor 5299. The beech and oak sawdust extracts intensified the synthesis of laccase, peroxidase, and tyrosinase, which was strongly expressed in T. versicolor 353, so it was chosen for further experiments with submerged cultivation. Conclusions. Birch, beech, and oak sawdust extracts can be used to increase the accumulation of T. versicolor biomass while beech and oak sawdust extracts are preferable for the intensification of the synthesis of oxidase-type enzymes.